HPV16 E6/E7 expression in circulating tumor cells in oropharyngeal squamous cell cancers: A pilot study - Economopoulou, P.; Koutsodontis,G.; Avgeris, M.; Strati,A.; Kroupis, C.; Pateras,I.; Kirodimos,E.; Giotakis,E.; Kotsantis,I.; Maragoudakis,P.; Gorgoulis,V.; Scorilas, A.; et al. (PLoS One, 2019)
OBJECTIVES: Human papillomavirus-related oropharyngeal squamous cell carcinoma (HPV+ OPSCC) is increasing in incidence. Although HPV+ OPSCC has favorable prognosis, 10 to 25% of HPV+ OPSCCs eventually recur. We sought to evaluate the feasibility of detection of HPV16 E6/E7 expression in Circulating Tumor Cells (CTCs) and its utility as a prognostic tool in HPV16-associated OPSCC. MATERIALS AND METHODS: We developed a highly sensitive RT-qPCR assay for HPV mRNA expression in EpCAM(+) CTCs. In 22 patients with early stage and locally advanced OPSCC we evaluated HPV16 E6/E7 expression in the EpCAM(+) CTC fraction at baseline and at the end of concurrent chemoradiotherapy. HPV status in pre-therapy formalin-fixed paraffin-embedded (FFPE) tumor biopsies was assessed by p16 immunohistochemistry and polymerase chain reaction (PCR) and double positives were subjected to Real-time qPCR assay for detection of HPV16, 18 and 31 types. RESULTS: Fourteen of 22 OPSCC (63.6%) were HPV DNA+/p16+. Among HPV+/p16+ patients, 10 patients (71.4%) were HPV16 DNA+. HPV16 E6/E7(+) CTCs were detected in 3 of 10 patients (30%) at baseline and 4 of 9 patients (44.4%) at the end-of-treatment, all of which were p16+/HPV16 DNA+. Survival analysis showed a significantly higher risk for disease relapse (p = 0.001) and death (p = 0.005) in patients with HPV16 E6/E7(+) baseline CTCs. CONCLUSION: Detection of HPV E6/E7(+) CTCs might be a useful noninvasive test in liquid biopsy samples for determination of a clinically relevant HPV infection in HPV+ OPSCC. Combined interpretation of HPV E6/E7(+) CTCs with UICC staging data may lead to alteration of risk definition of patient subsets, with improved risk discrimination in early-stage disease.
Keywords: Carcinoma, Squamous Cell/pathology/*virology; DNA, Viral/genetics; Female; Human papillomavirus 16/*genetics; Humans; Male; Neoplasm Recurrence, Local/genetics/virology; Neoplastic Cells, Circulating/*pathology; Oncogene Proteins, Viral/*genetics; Oropharyngeal Neoplasms/pathology/*virology; Papillomavirus E7 Proteins/*genetics; Papillomavirus Infections/pathology/virology; Pilot Projects; Prognosis; Repressor Proteins/*genetics; RNA, Messenger/genetics